Disease Phenotype and Outcome Depending on the Age at Disease Onset in Patients Carrying the R92Q Low-Penetrance Variant in TNFRSF1A Gene - Ruiz-Ortiz, Estíbaliz; Iglesias, Estíbaliz; Soriano, Alessandra; Buján-Rivas, Segundo; Español-Rego, Marta; Castellanos-Moreira, Raul; Tomé, Adrià; Yagüe, Jordi; Antón, Jordi; Hernández-Rodríguez, José (Frontiers in Immunology, 2017)
Background: Tumor necrosis factor-associated periodic syndrome (TRAPS) is an autosomal dominant autoinflammatory disease caused by mutations in the TNFRSF1A gene. R92Q, a low-penetrance variant, is usually associated with a milder TRAPS phenotype than structural or pathogenic mutations. No studies differentiating R92Q-related disease in patients with pediatric and adult onset have been performed to date. Objective: To analyze clinical features and disease outcomes in patients diagnosed with TRAPS associated to R92Q variant, and to investigate differences between patients with pediatric and adult disease onset. Methods: A retrospective review of patients with R92Q-related disease from four reference centers for autoinflammatory diseases was performed. Clinical and laboratory features, family history of autoinflammatory diseases, treatments received and outcomes during follow-up were recorded and separately analyzed in pediatric and adult patients. Our results were included in the analysis with other reported pediatric and adult R92Q-related disease series. Results: Our series encompassed 18 patients (9 female and 9 male) with R92Q variant. In 61% of patients, disease onset occurred during infancy and in 39%, during adulthood; with a median diagnostic delay of 5 years and a follow-up of 5.4 years. A positive family history of autoinflammatory disease was detected in 28% of patients. All patients presented with febrile recurrent episodes. Other common symptoms included arthralgia/arthritis (61%), myalgia (39%), asthenia/fatigue (44%), abdominal pain (39%), headache (33%), odynophagia (33%), skin rash (28%) and chest pain (22%). During attacks, 80% of patients increased acute phase reactants levels. No patient had developed amyloidosis during the study period. At the end of follow-up, 28% of patients were asymptomatic and treatment-free, 50% were receiving NSAIDs or glucocorticoids on-demand and 22% were being treated with biologic agents. When differences between pediatric and adult patients were globally analyzed, adults tended to have longer attacks duration and presented more frequently with chest pain and headache, while abdominal pain, vomiting, cervical adenitis and pharyngitis predominated in pediatric patients. No differences in outcomes and treatment requirements were observed in both age groups. Conclusions: This study has contributed to characterize R92Q-related disease by identifying trends in disease phenotypes depending on the age at disease onset.